Bacillus Calmette-Guerin pneumonitis after intravesical instillation: Report of two cases and a review of the literature - Spisarova, Martina; Losse, Stanislav; Jakubec, Petr; Hartmann, Igor; Kral, Milan; Ehrmann, Jiri; Szkorupa, Marek; Studentova, Hana; Melichar, Bohuslav (Biomedical papers, 2024)
Objective. Intravesical administration of bacillus Calmette-Guerin is standard adjuvant treatment of non-muscle invasive bladder cancer. In spite of the fact that this immunotherapy is locoregional, there are still risk of some complications. Methods. We describe two cases of systemic BCG infection after intravesical administration of BCG vaccine in patients with early stage of bladder cancer. Results. Both patients suffered from systemic BCG infection manifesting as BCG pneumonitis. After standard therapy with antituberculotic agents, both of them fully recovered. Conclusion. BCG infection can occur as a rare but potentially serious complication of this treatment procedure. Gravity of this side effect and its specific therapy require prompt and right diagnosis.
Keywords: bacillus Calmette-Guerin; bladder cancer; intravesical therapy